CasODE: Modeling Irregular Information Cascade via Neural Ordinary Differential Equations (Student Abstract) - Cheng, Zhangtao; Xu, Xovee; Zhong, Ting; Zhou, Fan; Trajcevski, Goce (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Predicting information cascade popularity is a fundamental problem for understanding the nature of information propagation on social media. However, existing works fail to capture an essential aspect of information propagation: the temporal irregularity of cascade event -- i.e., users' re-tweetings at random and non-periodic time instants. In this work, we present a novel framework CasODE for information cascade prediction with neural ordinary differential equations (ODEs). CasODE generalizes the discrete state transitions in RNNs to continuous-time dynamics for modeling the irregular-sampled events in information cascades. Experimental evaluations on real-world datasets demonstrate the advantages of the CasODE over baseline approaches.